Neutron Detectors: Cesium Lead Bromide (CsPbBr3) Thin‐Film‐Based Solid‐State Neutron Detector Developed by a Solution‐Free Sublimation Process (Adv. Mater. Technol. 12/2020). Issue 12 (9th December 2020) - Fernandez‐Izquierdo, Leunam; Reyes‐Banda, Martin Gregorio; Mathew, Xavier; Chavez‐Urbiola, Iker Rodrigo; El Bouanani, Lidia; Chang, Joseph; Avila‐Avendano, Carlos; Mathews, Nini Rose; Pintor‐Monroy, Maria Isabel; Quevedo‐Lopez, Manuel
Abstract : A Ga2 O3 /CsPbBr3 solid‐state diode for indirect neutron detection is demonstrated by Manuel Quevedo‐Lopez and co‐workers in article number 2000534 . This is enabled by a novel solvent‐free deposition method that allows CsPbBr3 films with pure CsPbBr3 perovskite phase, controlled stoichiometry and large grains.